Dynamics of Fulfillment: A Comparative Exploration of Life Satisfaction in European Muslim and Christian Communities - Özlem Yorulmaz; Leyla Zeynep Verçin (Journal of Economy Culture and Society)
Life satisfaction has become an important indicator for understanding the welfare level of countries, particularly today when immigration is increasing for various reasons such as war and the desire for better living conditions, good job opportunities, and high-quality education. This study investigates the life satisfaction of people who have left their community and established a new life at the expense of being a foreigner and a member of a minority community. In this study, the data of people living in Europe were used. Since the dominant religion in Europe is Christianity, Muslims are considered a minority. The study selects Islam as one of the minority religions in Europe and examines whether the life satisfaction of people who state that they are Muslim differs from that of non-minority Christians. For this purpose, ten countries with Muslim minorities were selected from the data of the European Social Survey (ESS). The life satisfaction of two groups, Muslim minority and Christians, was analyzed through a path model, which consists of socio-economic indicators, and the trust component, using the path analysis method. Age, income, interpersonal trust, and governmental trust indicators were significant variables in both groups. Unexpectedly, religiosity was shown to have a positive effect on life satisfaction only for the Christian group and had no significant effect for the Muslim minority group.